First report from the Czech national registry of inborn errors of immunity (2012–2025) - Chovancova, Zita; Hlavackova, Eva; Hakl, Roman; Milota, Tomas; Kralickova, Pavlina; Malkusova, Ivana; Hutyrova, Beata; Safarova, Michaela; Vydlakova, Jana; Jilek, Dalibor; Novak, Jiri; Schneiderova, Helena; et al. (Frontiers in Immunology, 2025)
IntroductionCongenital immune system defects represent an ever-growing group of diseases characterized by increased susceptibility to infections and association with autoimmune, autoinflammatory, allergic and malignant complications. Here, we provide the first comprehensive report on inborn errors of immunity (IEIs) in Czechia based on the analysis of patient data from the Czech national registry (CzNR) of IEIs.Material and methodsThe online platform of CzNR of IEIs was established in 2012, compiling data about epidemiology, type of diagnosis, clinical and laboratory parameters, as well as the treatment of patients diagnosed with IEIs since 1981.ResultsThe total of 1,443 registered patients includes 697 males (48.3%) and 746 females (51.7%). The median age at diagnosis was 21.0 (0–86) years. The most represented group of patients was those with antibody deficiencies (788 patients; 54.6%). This was followed by complement deficiencies (242; 16.8%), combined immunodeficiencies with syndromic features (250; 17.3%), combined immunodeficiencies (55; 3.8%), congenital defects of phagocyte number, function, or both (31; 2.1%), autoinflammatory disorders (28; 1.9%), immune dysregulation diseases (24; 1.7%), intrinsic and innate immunity defects (21; 1.5%), primary immunodeficiency phenocopies (3; 0.2%), and bone marrow failure disorders (1; 0.1%). Common variable immunodeficiency (504; 34.9%), hereditary angioedema (222; 15.4%), and DiGeorge syndrome (182; 12.6%) were the most frequent diagnoses.ConclusionIn this article, we report the epidemiology of IEIs in the Czech Republic for the first time based on the CzNR of IEIs data. The prevalence of IEIs is approximately 13.2 patients per 100000 inhabitants of the Czech Republic.